Statin Treatment in Patients With Stroke With Low‐Density Lipoprotein Cholesterol Levels Below 70 mg/dL - Joon‐Tae Kim; Ji Sung Lee; Beom Joon Kim; Jihoon Kang; Keon‐Joo Lee; Jong‐Moo Park; Kyusik Kang; Soo Joo Lee; Jae Guk Kim; Jae‐Kwan Cha; Dae‐Hyun Kim; Tai Hwan Park; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Background It is unclear whether statin treatment could reduce the risk of early vascular events when baseline low‐density lipoprotein cholesterol (LDL‐C) levels are already low, at <70 mg/dL, at the time of the index stroke. Methods and Results This study was an analysis of a prospective, multicenter, nationwide registry of consecutive patients with first‐ever acute ischemic stroke with baseline low‐density lipoprotein cholesterol levels <70 mg/dL and without statin pretreatment. An inverse probabilities of treatment weights method was applied to control for imbalances in baseline characteristics. The primary outcome was a composite of stroke (either hemorrhagic or ischemic), myocardial infarction, and all‐cause death within 3 months. A total of 2850 patients (age, 69.5±13.4 years; men, 63.5%) were analyzed for this study. In‐hospital statin treatment was used for 74.2% of patients. The primary composite outcome within 3 months occurred in 21.5% of patients in the nonstatin group and 6.7% of patients in the statin group (P<0.001), but the rates of stroke (2.65% versus 2.33%), hemorrhagic stroke (0.16% versus 0.10%), and myocardial infarction (0.73% versus 0.19%) were not significantly different between the 2 groups. After inverse probability of treatment weighting analysis, the primary composite outcome was significantly reduced in patients with statin therapy (weighted hazard ratio [HR], 0.54 [95% CI, 0.42–0.69]). However, statin treatment did not increase the risk of hemorrhagic stroke (weighted HR, 1.11 [95% CI, 0.10–12.28]). Conclusions Approximately three‐quarters of the patients with first‐ever ischemic stroke with baseline low‐density lipoprotein cholesterol levels <70 mg/dL received in‐hospital statin treatment. Statin treatment, compared with no statin treatment, was significantly associated with a reduced risk of the 3‐month primary composite outcomes and all‐cause death but did not alter the rate of stroke recurrence.